China and the Indo-Pacific in India-Asean ties : prospects for ASEAN - Angelina Gurunathan; Ravichandran Moorthy (Penerbit Universiti Kebangsaan Malaysia, 2021)
India’s trading ties with Southeast Asian nations started in ancient times, sustained during the colonial times and later rekindled in the post-Cold War era. Since India embarked on major economic reforms in 1991, economic partnership had been important in India’s engagements with ASEAN. Nevertheless, the multipolar world of the 21st century had also given rise to new emerging geopolitical realities that inevitably influence the economic domain of the partnership. The main issue this article attempts to address is how in a multipolar world, China influences India’s strategic partnership with ASEAN. The main objective of this endeavour is to highlight the key global dynamics in view of China’s rise mainly related to the Indo-Pacific that shape India’s partnership with ASEAN; and the opportunities for ASEAN in its ties with India moving forward. This is analysed from the conceptual framework of strategic hedging to highlight how the US-China competition of the post-Cold War era influences the foreign policy outlook of India, shaping India’s approach towards ASEAN. The methodology employed for this analysis is a qualitative analysis of primary data obtained from official publications of government websites and portals. Analysis is undertaken chronologically and further substantiated with secondary data from scholarly works, as well as news articles. The findings reveal that since independence, China has featured strongly in India’s geopolitical strategies and therefore China’s strong economic footprints within ASEAN have much bearing on India’s policies towards ASEAN. Nevertheless, India’s strengthening partnership with the major powers of the world within the Indo-Pacific framework also has the potential for spin-off effects for ASEAN’s economic as well as strategic benefits. In conclusion, the developments related to the Indo-Pacific in view of China’s rise, indicate a positive outlook for India-ASEAN partnership which ASEAN could leverage on.